Dialogue on Dialogue - Alhasawi, Nourah Abdullah M. (Journal of ecumenical studies, 2018)
The article focuses on Saudi Islamic Studies academics, many of them are considered to be religious leaders with enough influence to promote interreligious dialogue (IRD) and to encourage its acceptance among Saudis. It reports that introducing IRD to Islamic Studies through academic work could be the most practical way to confront their disinclination and to build trust.